ANALISIS KESEHATAN KEUANGAN USAHA KECIL DAN MENENGAH (UKM) BATIK SELOKA ADIPALA KECAMATAN ADIPALA KABUPATEN CILACAP - Mutia Pamikatsih (Universitas Nahdlatul Ulama Al Ghazali Cilacap, 2022)
Small and Medium Enterprises (SMEs) in the industrial era 4.0 are increasingly widespread and require creation and creativity to support competitiveness in the market, industrial and local wisdom sectors. Many Small and Medium Enterprises (SMEs) in the modern era like today are increasingly flocking to compete in creating their works. In line with the many cultures that are owned by the Indonesian state, such as dance arts, music arts, sculptural arts, written batik arts. However, in reality, there are many arts in Indonesia that are often imitated by other countries. The purpose of writing this assignment is to find out how the financial management of UKM Batik Seloka is. The main problem that is the focus of the development of Seloka Batik SMEs in Adipala Village is regarding financial management. Financial governance in most SMEs still uses a manual system without the help of a computer. There are several Batik SMEs that use computers but most still use manuals.